Beyond the egg drop : infusing engineering into high school physics - Eisenkraft, Arthur, ....- (Arlington : NSTA Press, 2018)
Problem: You're eager to expand your physics curriculum and engage your students with engineering content but you don't know how. Solution: Use the approach and lessons in Beyond the Egg Drop to infuse engineering into what you're already teaching, without sacrificing time for teaching physics concepts. In addition to a thorough discussion on the rationale, justification, meaning, and implementation of integrating engineering into your science curriculum, this book provides 24 flexible, engineering-infused physics lessons that cover mechanics, optics, electricity, and thermodynamics. Lessons also include examples of student work; incorporate strategies for assessment, teaching, and student learning; and connect to A Framework for K–12 Science Education and the Next Generation Science Standards. 　 And like the venerable egg-drop experiment, these are classroom-tested lessons that are designed to truly engage your students. You can tell your students will tune in from the lesson titles—from “Bumper Cars” to “Zombie Apocalypse Flashlight.” Developed as part of Project Infuse, a National Science Foundation study, the lessons in Beyond the Egg Drop will make it easier to include engineering concepts and skills without having to restructure your existing physics curriculum.